Axl and EGFR Dual-Specific Binding Affibody for Targeted Therapy in Nasopharyngeal Carcinoma - Saidu Kamara; He Wen; Yanru Guo; Ying Liu; Lei Liu; Wangqi Du; Jun Chen; Shanli Zhu; Lifang Zhang (Cells)
Nasopharyngeal carcinoma (NPC) is a tumor of the head and neck, with a higher incidence in southern China and Southeast Asia. Radiotherapy and chemotherapy are the main treatments; however, metastasis and recurrence remain the main causes of treatment failure. Further, the majority of patients are diagnosed in the late stage due to lack of tumor-specific biomarker for early diagnosis. Therefore, an effective treatment and early detection can improve the outcome of patient with NPC. Axl and EGFR are co-expressed in NPC tissues and play key roles in tumor proliferation, migration, and invasion, which are often correlated with poor prognosis and therapy resistance. In this study, we generated a novel bispecific affibody (Z239-1907) for the dual targeting and inhibition of Axl and EGFR expression in NPC-positive cells both in vitro and in vivo. The in vitro experiments demonstrated that Z239-1907 had more pronounced antitumor effects than either modality alone (ZAXL239 or ZEGFR1907) in NPC-positive cells. Further, mice bearing NPC-positive tumors showed significant inhibition in tumor growth after treatment with Z239-1907 compared to ZAXL239 and ZEGFR1907. The in vivo tumor targeting ability and imaging also showed that Z239-1907 specifically and selectively targeted NPC xenograft mice models and accumulate at tumor site as early as 30 min and disappeared within 24 h post-injection. Collectively, these results suggest that Z239-1907 dual-target affibody is a promising therapeutic agent and a molecular imaging probe for early diagnosis in NPC.